Obstetric Bleeding Curriculum - Julia Metzner; Jennifer Reid; Christopher Wu; Stefan Lombaard; Michael Fialkow; Megan Sherman; Sara Kim (Association of American Medical Colleges, 2011)
Abstract One out of ten deliveries are complicated by postpartum hemorrhage (PPH) with an associated maternal mortality rate as high as 17%. The most common cause of PPH is uterine atony. Uterine atony, or failure of the myometrial muscle fibers to contract following delivery, can lead to rapid and severe hemorrhage and hypovolemic shock. The effective management of major PPH relies on an organized multidisciplinary approach involving the obstetrician, anesthesiologist, hematologist, nursing staff, laboratory, and blood bank personnel. This simulation was been designed to provide an opportunity for anesthesia and OB/GYN residents to practice the diagnosis and management of an obstetric bleeding emergency in a realistic, but risk-free environment. This simulation scenario has been implemented successfully in our simulation curriculum at University of Washington ISIS Simulation Center. It is best run in a standard simulation center with a high-fidelity mannekin (Laerdal SimMan). The simulation takes two hours to complete and works best with three-to five-learners per session. Participants at the institution, first-, second-, and third-year clinical anesthesia residents, acknowledged the realism and value of the experience in their feedback. Perceived benefits included optimization of clinical performance and decision-making during crisis management, and a sharpening communication skills while interacting with a multidisciplinary team.